Pengaruh Kompetensi, Peran Aparat Desa, Dan Pemanfaatan Teknologi Informasi Terhadap Akuntabilitas Pengelolaan Keuangan Desa Di Kecamatan Ujan Mas - Puspa Rini; Sucipto Febrianto; Novriza Wahyu Ardiyansyah (Jurnal Ilmiah Raflesia Akuntansi, 2025)
The presence of accountability in financial management is indicative of strong governance. The accountability principle must be implemented by the village administration in order to hold the village community accountable for its financial management. The utilization of information technology, the involvement of village authorities, and competency are some other elements that affect accountability. This study's survey was limited to the communities in the Ujan Mas District. 64 village finance managers, including village heads, village secretaries, financial heads, and planning heads, made up the sample for this quantitative study. The SPSS version to manage and check survey data by utilizing 30 software programs. the study used primary data as its data type the apparatus's proficiency has a negative and substantial the role of village officials has been demonstrated to prossess a positive and have a significant impact on responsibulity in village financial management, as well as technology used which also provides on that is positive and significant contribution to increasing acoountability in village financial management.